ChemInform Abstract: C—H Functionalization of Triazolo[a]‐Annulated 8‐Azapurines. Issue 37 (August 2016) - Gorbunov, Evgeny B.; Rusinov, Gennady L.; Ulomsky, Evgeny N.; Rusinov, Vladimir L.; Charushin, Valery N.; Chupakhin, Oleg N.
Abstract: Direct C—H functionalization of triazolo[a]‐annulated 8‐azapurines with phenol ethers or thiophene is performed using the oxidative nucleophilic displacement of a hydrogen on the pyrimidine ring, proceeding through the intermediacy of the corresponding σ H —adducts.